2022
DOI: 10.31822/jomat.2022-7-1-81
|View full text |Cite
|
Sign up to set email alerts
|

Determining destination risk perceptions, their effects on satisfaction, revisit and recommendation intentions: Evidence from Sanliurfa/Turkey

Abstract: Visitors' risk perception plays a vital role in their destination choice, intention to return, satisfaction and recommendations to others. At the same time, perceived risks affect destination image, which in turn causes increased or decreased demand for attractions of destinations. The aim of this study is to determine risk dimensions and their effects on recommendation and revisit intentions. Scale is most widely used in tourism research. This scale consists of six dimensions, namely, physical, time, social, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…When these findings are examined within the scope of the theory of planned behavior, it can be concluded that if the tourists visiting Gaziantep are sufficiently involved in culinary culture and gastronomy activities, customer satisfaction can be achieved, and thus positive behavioral intentions can be developed in customers. It is because, as mentioned before, intentions determine whether a person has sufficient motivation to perform a certain behavior (Mancı, 2022).…”
Section: Discussion Of the Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…When these findings are examined within the scope of the theory of planned behavior, it can be concluded that if the tourists visiting Gaziantep are sufficiently involved in culinary culture and gastronomy activities, customer satisfaction can be achieved, and thus positive behavioral intentions can be developed in customers. It is because, as mentioned before, intentions determine whether a person has sufficient motivation to perform a certain behavior (Mancı, 2022).…”
Section: Discussion Of the Resultsmentioning
confidence: 94%
“…Perceived behavioral control represents people's belief in their ability to control their actions. Intentions determine whether a person has sufficient motivation to perform a specific behavior (Mancı, 2022). Finally, personal characteristics refer to the individual factors that influence people's behaviors (Ajzen, 1991).…”
Section: Theoretical Basismentioning
confidence: 99%
“…Given that local residents are one of the most significant stakeholders in destination management (Mancı, 2022), establishing their attitudes about the development of tourism activities is a critical issue. As a result, the perceptions of local people in Mersin Province about the development of tourism activities were measured in this study.…”
Section: Resultsmentioning
confidence: 99%
“…This study is based on both secondary and primary data. Primary data is collected through an adapted questionnaire (Bariar & Jain, 2020;Konecnik & Gartner, 2007;Manci, 2022;Shen & Ma, 2022), which contains a variety of questions related to demography and destination brand equity. This questionnaire is developed using Google Forms and distributed by e-mail.…”
Section: Methodsmentioning
confidence: 99%
“…For this purpose, the concept of brand equity is applied for tourism destination by examining its four dimensions (Konecnik & Gartner, 2007), that are Destination Awareness (DA), Destination Image (DI), Destination Perceived Quality (DPQ), and Destination Loyalty (DL). An additional dimension Destination Perceived Risk (DPR) (Manci, 2022) is added for better understanding of the COVID-19 condition. As a result, this research includes four main objectives:…”
Section: Research Purpose and Objectivesmentioning
confidence: 99%